2013
DOI: 10.1094/pdis-02-13-0132-re
|View full text |Cite
|
Sign up to set email alerts
|

Sensitive and Direct Detection of Heterodera filipjevi in Soil and Wheat Roots by Species-Specific SCAR-PCR Assays

Abstract: Cereal cyst nematodes are the most important plant-parasitic nematodes on cereal crops in wheat producing areas of the world. Heterodera filipjevi was first reported in China in 2010. In this study, species-specific sequence characterized amplified region–polymerase chain reaction (SCAR-PCR) assays for detection and identification of H. filipjevi from infected wheat roots and soil were developed. The species-specific primers were designed according to the randomly amplified polymorphic DNA (RAPD) markers ampli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 27 publications
1
14
0
Order By: Relevance
“…The direct detection of plant nematodes using DNA from infected plant tissues has been published2731323334, although those methods for preparing nucleic acids require toxic reagents and expansive instruments. In this study, direct extraction of DNA from plant root galls greatly improved the efficiency when using the FTA technology.…”
Section: Discussionmentioning
confidence: 99%
“…The direct detection of plant nematodes using DNA from infected plant tissues has been published2731323334, although those methods for preparing nucleic acids require toxic reagents and expansive instruments. In this study, direct extraction of DNA from plant root galls greatly improved the efficiency when using the FTA technology.…”
Section: Discussionmentioning
confidence: 99%
“…Studies with other nematode species such as cyst nematode and root-knot nematodes also found that a single nematode could be used for nematode species detection by real-time PCR assay (Madani et al 2005;Toyota et al 2008). In a sensitivity analysis for H. filipjevi detection, Peng et al (2013) detected 1/160 of a juvenile, 1/5,120 of a female, and 5 × 10 −4 of a cyst by a speciesspecific sequence-characterized amplified region PCR assay.…”
Section: Discussionmentioning
confidence: 99%
“…Cereal cyst nematodes (CCNs, Heterodera spp.) are sedentary plant-parasitic nematodes that infect cereal food crops such as wheat ( Triticum aestivum) ), barley ( Hordeum vulgare ) and oat ( Avena sativa ) [ 1 , 2 ]. CCNs occur in most wheat-growing regions worldwide and cause serious yield losses globally, thereby being major pests affecting the world’s food supply [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%